Elastic Properties Of Toughened Mussel Epoxy Under Aged And Unaged Conditions - Jason Ling Ji Chung; Nornashima Binti Md Ali (Journal of Structural Monitoring and Built Environment, 2026)
This study investigates the mechanical behavior of silane-treated mussel powder modified epoxy (SMPME) composites under dry and hydrothermally aged conditions (60°C, 50 days). The effects of filler volume fraction on tensile properties, including elastic modulus, Poisson’s ratio, and tensile strength, were evaluated using dog-bone specimens. Results show that SMPME generally enhances mechanical performance, with a non-linear trend and an optimal filler content. After aging, an overall improvement in properties was observed, attributed to post-curing and improved filler–matrix interfacial bonding. Although absolute values are lower than literature due to fabrication-related factors, the trend remains consistent. Overall, SMPME demonstrates strong potential as a sustainable reinforcement for epoxy composites